Hyperventilation strain CMR imaging in patients with acute chest pain - Siry, Deborah; Riffel, Johannes; Salatzki, Janek; André, Florian; Ochs, Marco; Weberling, Lukas D.; Giannitsis, Evangelos; Katus, Hugo; Friedrich, Matthias (Scientific reports, 2022)
In patients with suspected acute coronary syndrome high-sensitivity cardiac tropnonin T is used for rapid patient triage. Some acute coronary syndrome patients assigned to the observe zone based on high-sensitivity cardiac troponin T after 1 h require further diagnostic testing. Fast-strain encoded CMR imaging with breathing maneuvers may accelerate diagnostic work-up and identify patients suffering from acute coronary syndrome. Patients presenting with acute chest pain (high-sensitivity cardiac troponin T level 5-52 ng/L) were prospectively enrolled (consecutive sampling, time of recruitment: 09/18-06/19). Fast-strain-encoded imaging was performed within the 1-h timeframe (0 h/1 h algorithm) prior to 2nd high-sensitivity troponin T lab results. Images were acquired at rest as well as after 1-min of hyperventilation followed by a short breath-hold. In 108 patients (59 male; mean age: 57 ± 17y) the mean study time was 17 ± 3 min. An abnormal strain response after the breathing maneuver (persistent/increased/new onset of increased strain rates) correctly identified all 17 patients with a high-sensitivity troponin T dynamic (0 h/1 h algorithm) and explanatory significant coronary lesions, while in 86 patients without serologic or angiographic evidence for severe coronary artery disease the strain response was normal (sensitivity 100%, specificity 94.5%; 5 false positive results). The number of dysfunctional segments (strain > − 10%) proved to be a quantifiable marker for identifying patients with acute coronary syndrome. In patients with suspected acute coronary syndrome and inconclusive initial high-sensitivity troponin T, fast-strain-encoded imaging with a breathing maneuver may safely and rapidly identify patients with acute coronary syndrome, without the need for vasodilators, stress, or contrast agents.